Developing entrepreneurial behaviours through entrepreneurship education - Fernando, M.S.J.; Nishantha, B. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
The purpose of this study is to explore the impact of social learning in entrepreneurship education on the development of entrepreneurial behaviours of course participants and how this impact is moderated by the level of self-directed learning. Primary data were collected from students of extension courses on entrepreneurship offered by three state-sector universities in Sri Lanka. The results show that social learning plays a vital role in entrepreneurship education and it positively impacts the development of entrepreneurial behaviours. That impact is increased when it is moderated by the level of self-directed learning of course participants except in the resource combination aspect of entrepreneurial behaviours. The research provides important insights into the higher education sector in framing the delivery of its entrepreneurship courses and the selection of course participants to ensure effectiveness in entrepreneurship education. Entrepreneurs should engage in social learning in entrepreneurship education to develop their entrepreneurial learning. This study affirms existing arguments on the association between social learning and entrepreneurship development through a quantitative analysis, expanding that framework to include a moderating effect by the level of self-directed learning of potential and practising entrepreneurs.
Keywords: entrepreneurial behaviours, entrepreneurship education in Sri Lanka, social learning, selfdirected learning